THE INFLUENCE OF FEAR OF COVID-19, MEDIATED BY PSYCHOLOGICAL DISTRESS, WITH ORGANIZATIONAL SUPPORT AS A MODERATOR, IMPACTS EMPLOYEE WELL-BEING - REHMAN , SU; REHMAN , AU; ELAHI , A; RAFIQ , M; KHAN , R; JAFFAR , F; AIN , QU; AWAN , S; MUJAHID , MUF; RAHIM , N; et al. (Biological and Clinical Sciences Research Journal, 2023)
The main objective of this research was to investigate how fear of COVID-19 affects the mental well-being of employees in Lahore. The study considered two important factors: the potential mediating effect of psychological distress and the potential moderating effect of perceived organizational support, and aimed to establish connections between these variables. The study gathered data from 324 participants from the public sector, regardless of gender, occupation, or job status, using convenient sampling methods and Google Forms and questionnaires. The results showed that individuals working in healthcare and the general public who experience increased levels of fear about COVID-19 are more likely to have compromised mental health. However, perceived organizational support was found to have no significant potential to alleviate the negative impact of psychological distress on employees’ mental health. It is important to note that the study’s conclusions are specific to the population surveyed in Lahore, as the research was limited to a single city in Punjab and the sample size was small. Future research could focus on strategies to mitigate fear during pandemics, thereby improving the overall quality of life for individuals. This study highlights that emergencies such as the fear generated by COVID-19 can negatively impact both physical and psychological health among employees. Therefore, it is recommended that healthcare workers and other professionals receive training to enhance their resilience in the face of such emergencies. This research fills a gap in current knowledge by examining the management of pandemic-related fear and its consequent negative impacts, while also highlighting the crucial role of perceived organizational support. Additionally, the study emphasizes the intermediary function of psychological distress in this context.